Railway Slang in Internet Communication - Мосьпан, Елена Павловна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
Main theme groups of not codified railway lexicon and their relative quantitative structure are described. Most frequent in Internet discourse types of nominations from these groups are established. Genre features of some active slangy nominations using are defined. Influence of communication participants’ status and lexical units’ connotation type on choice of nomination is proved. New slangy nominations are revealed. Conclusions on the field of professional popular speech use are drawn.